Enhancing Arabic Language Proficiency through Nested Curriculum Integration: A Qualitative Case Study at Diniyyah Puteri Padang Panjang, Indonesia - Febriani, Suci Ramadhanti; Asrori, Imam; Sutaman, Sutaman (Jurnal Pendidikan Islam, 2025)
Purpose – The limited time allocated for Arabic language instruction within the Ministry of Religious Affairs curriculum encouraged Diniyyah Puteri Padang Panjang to implement curriculum integration to enhance students’ Arabic proficiency. This study aims to explain the implementation of the integration between the 2019 Ministerial Decree Curriculum (KMA) and the Diniyyah Arabic Center (DAC) Curriculum. Design/methods/approach – This study employs a qualitative approach with a case study method. Data were collected through classroom observations, in-depth interviews with four Arabic teachers, the principal, and the head of DAC, as well as documentation techniques. Data analysis was conducted through data collection, condensation, presentation, and conclusion drawing. Findings – The findings reveal that the curriculum integration at Diniyyah Puteri adopts a Nested Curriculum model characterized by: (1) Integrated learning objectives, including Arabic language skills and linguistic elements; (2) Learning materials that include both the official Ministry textbooks and supplementary resources such as Arabic camp programs, vocabulary enhancement, and muhadatsah mastery; (3) Time allocation combining two hours of formal instruction with non-formal learning within school and dormitory settings; (4) Learning activities that span classroom, dormitory, and school environment practices. The integration model contributes significantly to improved speaking and reading skills, as evidenced by students' increased interaction with native speakers and their readiness for further studies in the Middle East. Research implications – Despite these advancements, the integration model faces challenges related to the lack of a structured instructional system, indicating the need for systematic development in curriculum design and implementation frameworks.